STUDY OF DRUG UTILIZATION PATTERN OF ANTIEPILEPTIC DRUGS AT TERTIARY CARE HOSPITAL - Rahul Wagh, Sudhir Padwal, Shrikant Dharmadhikari,Vinod Deshmukh (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
The World Health Organization (WHO) defined Drug Utilization Research(DUR) in 1977 as “The advertising, dissemination, prescription, and utilization of drugs in asociety, with an exceptional accentuation on the subsequent medical, social and monetaryresults.